Analysis of pediatric assent information in early-phase cancer clinical trials through a children’s research advisory group - Mínguez-Garrido, Ana; Moriconi, Valeria; Vergara-Muñoz, Beatríz; Buendía-López, Susana; Andión, Maitane; Herrero, Blanca; Luengo, Mirian; Rubio-San-Simón, Alba (Frontiers in Psychology, 2025)
IntroductionThis study aims to identify potential barriers to children’s proper understanding of informed assent forms and to evaluate alignment with existing guidelines.Material and methodsThe KIDS Madrid Young People Advisory Group (YPAG) reviewed six pediatric oncology trial assent forms using a structured questionnaire. Investigators provided item-specific weightings. Quantitative and qualitative data were integrated.ResultsThe analysis showed moderate satisfaction overall. Strengths included clarity in describing the trial purpose and risks/benefits. Key deficiencies were found in accessibility features such as audiovisual aids, and simplified language. Investigators prioritized technical accuracy, while KIDS emphasized clarity, structure, and engagement. Gaps were identified in adherence to existing guidelines, especially regarding document length, readability, and support resources.DiscussionThere is a clear mismatch between investigators’ focus and young patients’ needs. While technical content was generally adequate, critical elements for child comprehension were lacking. These findings support the need to involve YPAGs to improve pediatric assent documents.